I worked it out to be c = -13.
On to part 2!
Would I work it out the same as part 1? (i.e. solve for m when the discriminant = 0)
So far I've done:
mx + 6 = -2x^{2} - 6x +2
-2x^{2} - 6x - 4 - mx = 0
(I have a feeling this isn't correct.)
I worked it out to be c = -13.
On to part 2!
Would I work it out the same as part 1? (i.e. solve for m when the discriminant = 0)
So far I've done:
mx + 6 = -2x^{2} - 6x +2
-2x^{2} - 6x - 4 - mx = 0
(I have a feeling this isn't correct.)
The discriminant there would be (m + 6)^{2} - 32 which, solved for x, gives us -6 ±4√2 -- the correct answer.
Thanks for the help, Mark.
One final question: How do you properly type equations? I tried pasting them from Microsoft Equation 3.0 (via Word) but to no avail.